2018
DOI: 10.1089/hum.2017.064
|View full text |Cite
|
Sign up to set email alerts
|

Altered Long Non-Coding RNA Transcriptomic Profiles in Ischemic Stroke

Abstract: A previous study described the important regulatory roles of microRNAs (miRNAs) in ischemic stroke. However, the functional significance of long non-coding RNA (lncRNAs) in ischemic stroke was largely unknown. This study aimed to identify lncRNA profiling and elucidate the regulatory mechanisms in the pathophysiology of stroke. RNA sequencing was performed on the blood of three ischemic stroke patients and three normal controls. Differential expression analysis was used to identify differentially expressed lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 45 publications
1
34
2
1
Order By: Relevance
“…Studies have shown that ATP produced by glycolysis is vital for fast axonal transport of vesicles, synaptic ATP maintenance during energy stress, and energy requirement for action potential firing. 14,15 For example, the MEG3 expression is significantly elevated in focal cerebral ischemia mouse models and it mediates ischemic neuronal death in stroke by activating p53 or targeting the miR-21/PDCD4 signaling pathway. During ischemic attacks and acute glucose deprivation, glycolytic metabolism in the brain is impaired, leading to neuron death.…”
mentioning
confidence: 99%
“…Studies have shown that ATP produced by glycolysis is vital for fast axonal transport of vesicles, synaptic ATP maintenance during energy stress, and energy requirement for action potential firing. 14,15 For example, the MEG3 expression is significantly elevated in focal cerebral ischemia mouse models and it mediates ischemic neuronal death in stroke by activating p53 or targeting the miR-21/PDCD4 signaling pathway. During ischemic attacks and acute glucose deprivation, glycolytic metabolism in the brain is impaired, leading to neuron death.…”
mentioning
confidence: 99%
“…This analysis was conducted to provide functional implications of the candidate lncRNA ENSMUST00000160839 by analyzing its association with mRNAs. Although three biological replicates were used in co-expression analysis in previous studies [62][63][64][65], the increased sample size in the present study will help validate the results.…”
Section: Discussionmentioning
confidence: 67%
“…Further, the functional variant rs139365823 in pre-miR-138 enhanced the miR-138-mediated inhibitory regulation of DVL2 and conferred the risk for congenital heart disease in a Chinese population [38]. LncRNA LINC00884 was one of the top five lncRNAs with the largest numbers of ICM associations in the study of He et al [39].…”
Section: Icm Susceptibility Biomarkersmentioning
confidence: 91%